PENGARUH PEMBERIAN SUPLEMEN IKAN GABUS PADA STATUS NEUROLOGIS PASIEN STROKE ISKEMIK DI RUMAH SAKIT UMUM DAERAH PATUH PATUT PATJU - Dwi Monika Ningrum; Eka Septiani MS (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2021)
Stroke is the leading cause of death and disability in a world that requires treatment and care in the long term. Many factors that influence the outcome and the level of worsening after ischemic stroke include hypoalbumin which is one of the factors affecting the outcome of stroke. This study to determine the effect of supplementation of Snakehead fish on neurological improvement ischemic stroke patients at Patuh Patut Patju hospital. This study included quasi experimental research with Sparate Samples Pretest-Posttest design, Pre treatment ischemic stroke patients who have not given supplements of Snakehead fish (H1) and post treatment of ischemic stroke patients who have been given supplement Snakehead fish dose 3 times a day for 14 day (H14). Clinical outcome in grades of serum albumin levels, NIHSS and Barthel index. Analysis outcome with SPSS Shapiro wilk test, Wilcoxon signed test , and Mann whitney testOutcome post treatment decrease NIHSS score (p = 0,000, <0,05), increased Barthel index score (p = 0,000, <0,05), increased serum albumin level (p = 0.000, <0,05). Snakehead fish supplement can decrease NIHSS score, increase barthel index score and serum albumin level post given for 14 day.